Distribution, economic injury level and sequential sampling of leaf folder (Cnaphaiocrosis medinalis) on rice (Oryza sativa) - CHANDER, SUBHASH; SINGH, VIDYA SAGAR (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the rainy season of 1997 and 1998 to study the spatial distribution of leaf folder (Cnaphalocrosis medinalis Guenee) on rice (Oryza sativa L.) in terms of its damage using Taylor’s power law. The vahles of aggregation parameter (b*) < 1.0 indicated regular distribution of the pest on the crop. Linear regression model for yield infestation relationship was found to be y = 91.8182-1.0434 X (R2 = 0.58) anyÂ 100.1869-0.5036 X (R2= 0.88) during 2 years. Based on gain threshold of 0.39 tonne/ha and regression coefficient of yield-infestation model, economic injury level was determined as 4 % folded leaves during the first year and 8 % folded leaves during the second year at panicle-emergence stage of the crop. Sequential sampling plan was formulated using distribution parameters, economic injury level and error probability of 20 %.